Avaliação toxicológica e farmacológica não-clínica da fração alcaloídica de Sida rhombifolia L.: um estudo in silico e in vivo - Linhares, Thyfanne Suellen Tavares (2024)
Sida rhombifolia (Malvaceae) is a plant popularly known in Brazil as “matapasto”, “guaxuma” and “relógio”, being widely used by the Indian population for the treatment of high blood pressure, diabetes and gout. Alkaloid compounds have already been isolated from it, such as cryptolepinone and cryptolepine salt, which showed vasorelaxant and antioxidant activity in non-clinical trials in rodents. Doxorubicin (Dox) is an antibiotic widely used as an antineoplastic agent, and is the first-choice treatment for solid tumors and hematological malignancies. However, this drug has cardiotoxic events as one of its numerous side effects. In this context, clinical monitoring of the cardiac condition of these patients is carried out using echocardiographic examinations in order to analyze the cardiotoxic effects and seek alternatives to improve the prognosis. Therefore, the present study seeks to evaluate the toxicological effects and pharmacological effects (such as possible cardioprotection) of the alkaloid fraction obtained from Sida rhombifolia. Therefore, for the in silico study, the AdmetSAR tool was used to analyze the pharmacokinetic parameters of the alkaloids. For in vivo, adult Swiss mice (male and female) were used and treated with the alkaloid fraction (FrAlc) at a concentration of 200 mg/Kg, following OECD 407. In two groups of animals, cardiotoxicity was induced with administration of doxo in weekly cumulative doses, for four weeks, concomitantly with the use of FrAlc. Assessments of toxicological aspects, such as weight and consumption, and echocardiographic assessments were carried out weekly. As a result, the in silico study served as a basis for understanding some aspects and also generated questions that were resolved throughout the work. Due to the echocardiographic records not providing pattern recognition to verify the cardiotoxic effects caused by doxo, it was not possible to observe whether FrAlc (200 mg/kg) was capable of promoting a cardioprotective effect, however it was possible to infer that its use minimized some doxo induced events. It was also observed that FrAlc did not present relevant clinical changes or deaths, indicating low toxicity. Thus, FrAlc demonstrated favorable prospects, toxicologically, which makes it interesting in therapeutics and available for further studies on its pharmacological effects, especially with regard to its antioxidant potential.